2014
DOI: 10.3109/01942638.2014.957431
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Summer Camp Intervention for Children with Developmental Coordination Disorder

Abstract: The intensive, group-based summer camp may offer a valuable alternative to improve the functional skills of children with DCD, while providing other notable benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 34 publications
6
56
0
2
Order By: Relevance
“…Similarities exist between this study and Mandich et al (2003) who reported successful participation built confidence to try new activities. Zwicker et al (2015) further supports that the CO-OP approach offers the child the opportunity to develop confidence and self-esteem which facilitates their willingness to participate in new and challenging activities.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Similarities exist between this study and Mandich et al (2003) who reported successful participation built confidence to try new activities. Zwicker et al (2015) further supports that the CO-OP approach offers the child the opportunity to develop confidence and self-esteem which facilitates their willingness to participate in new and challenging activities.…”
Section: Discussionsupporting
confidence: 52%
“…Zwicker et al . () further supports that the CO‐OP approach offers the child the opportunity to develop confidence and self‐esteem which facilitates their willingness to participate in new and challenging activities.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…It is based on the belief that when a child guides himself through a problem-solving task by talking aloud, he/she learns to regulate behavior by learning how to identify a goal, develop a plan and evaluate the success of that plan (Sangster et al, 2005). Several studies have shown that the CO-OP intervention is effective in obtaining the goals chosen by children with DCD (Miller et al, 2001; Polatajko et al, 2001; Corcoran et al, 2005; Zwicker et al, 2015). …”
Section: Introductionmentioning
confidence: 99%